Snail Promotes Epithelial Mesenchymal Transition in Breast Cancer Cells in Part via Activation of Nuclear ERK2 - Smith, Bethany N. (Public Library of Science, 2014)
Snail transcription factor is up-regulated in several cancers and associated with increased tumor migration and invasion via induction of epithelial-to-mesenchymal transition (EMT). MAPK (ERK1/2) signaling regulates cellular processes including cell motility, adhesion, and invasion. We investigated the regulation of ERK1/2 by Snail in breast cancer cells. ERK1/2 activity (p-ERK) was higher in breast cancer patient tissue as compared to normal tissue. Snail and p-ERK were increased in several breast cancer cell lines as compared to normal mammary epithelial cells. Snail knockdown in MDA-MB-231 and T47-D breast cancer cells decreased or re-localized p-ERK from the nuclear compartment to the cytoplasm. Snail overexpression in MCF-7 breast cancer cells induced EMT, increased cell migration, decreased cell adhesion and also increased tumorigenicity. Snail induced nuclear translocation of p-ERK, and the activation of its subcellular downstream effector, Elk-1. Inhibiting MAPK activity with UO126 or knockdown of ERK2 isoform with siRNA in MCF-7 Snail cells reverted EMT induced by Snail as shown by decreased Snail and vimentin expression, decreased cell migration and increased cell adhesion. Overall, our data suggest that ERK2 isoform activation by Snail in aggressive breast cancer cells leads to EMT associated with increased cell migration and decreased cell adhesion. This regulation is enhanced by positive feedback regulation of Snail by ERK2. Therefore, therapeutic targeting of ERK2 isoform may be beneficial for breast cancer.